Aktivitas Antidiabetika Kombinasi Fraksi Etil Asetat Buah Pare (Momordica charantia L.) dan Rimpang - Zamzani, Irfan; Nugroho, Agung Endro; Widodo, Gunawan Pamudji (Jurnal Farmasi Indonesia, 2017)
Diabetes Mellitus type 2 can be caused by the resistance of tissue towards insulin accompanied by relative deficiency in insulin secretion. Insulin resistance factor can result from obesity. This research aims to investigate anti- diabetic activity of the compound of FEA of curcuma (Curcuma domestica Val) and bitter melon (Momordica charantia L.). Subjects of this research were 40 albino Wistar rats (Rattus norvegicus) aged 5-8 weeks. The rats were randomly grouped into 8 experimental groups in which each group consisted of'5 rats. The tested animals were divided into 6 groups, KG) metformin 45 mg/Kg BB, P1: FEA curcuma 10 mg/ 200g BB, P2: FEA bitter melon 04 mg/ 200g BB, P3: Compound of FEA curcuma : FEA bitter melon 5 : 0,8 mg/200g BB, P4: Compound of FEA curcuma : FEA bitter melon 10 : 04 mg/200g BB, and P5: Compound of FEA curcuma : FEA bitter melon (20 : 02mg9/200g BB). The animals were inducted with insulin resistance with the giving of HFD-fructose. Result showed that the compound of FEA of curcuma (Curcuma domestica Val) and FEA of bitter melon (Momordica charantia L.) had the activity of lowering blood glucose level: the best anti-diabetic activity was identified in the compound of FEA of curcuma and FEA of bitter melon at the dose of 20: 0,2m9g/200g BB in the rats with HFD- fructose.Diabetes Mellitus type 2 can be caused by the resistance of tissue towards insulin accompanied by relative deficiency in insulin secretion. Insulin resistance factor can result from obesity. This research aims to investigate anti- diabetic activity of the compound of FEA of curcuma (Curcuma domestica Val) and bitter melon (Momordica charantia L.). Subjects of this research were 40 albino Wistar rats (Rattus norvegicus) aged 5-8 weeks. The rats were randomly grouped into 8 experimental groups in which each group consisted of'5 rats. The tested animals were divided into 6 groups, KG) metformin 45 mg/Kg BB, P1: FEA curcuma 10 mg/ 200g BB, P2: FEA bitter melon 04 mg/ 200g BB, P3: Compound of FEA curcuma : FEA bitter melon 5 : 0,8 mg/200g BB, P4: Compound of FEA curcuma : FEA bitter melon 10 : 04 mg/200g BB, and P5: Compound of FEA curcuma : FEA bitter melon (20 : 02mg9/200g BB). The animals were inducted with insulin resistance with the giving of HFD-fructose. Result showed that the compound of FEA of curcuma (Curcuma domestica Val) and FEA of bitter melon (Momordica charantia L.) had the activity of lowering blood glucose level: the best anti-diabetic activity was identified in the compound of FEA of curcuma and FEA of bitter melon at the dose of 20: 0,2m9g/200g BB in the rats with HFD- fructose.Diabetes Mellitus type 2 can be caused by the resistance of tissue towards insulin accompanied by relative deficiency in insulin secretion. Insulin resistance factor can result from obesity. This research aims to investigate anti- diabetic activity of the compound of FEA of curcuma (Curcuma domestica Val) and bitter melon (Momordica charantia L.). Subjects of this research were 40 albino Wistar rats (Rattus norvegicus) aged 5-8 weeks. The rats were randomly grouped into 8 experimental groups in which each group consisted of'5 rats. The tested animals were divided into 6 groups, KG) metformin 45 mg/Kg BB, P1: FEA curcuma 10 mg/ 200g BB, P2: FEA bitter melon 04 mg/ 200g BB, P3: Compound of FEA curcuma : FEA bitter melon 5 : 0,8 mg/200g BB, P4: Compound of FEA curcuma : FEA bitter melon 10 : 04 mg/200g BB, and P5: Compound of FEA curcuma : FEA bitter melon (20 : 02mg9/200g BB). The animals were inducted with insulin resistance with the giving of HFD-fructose. Result showed that the compound of FEA of curcuma (Curcuma domestica Val) and FEA of bitter melon (Momordica charantia L.) had the activity of lowering blood glucose level: the best anti-diabetic activity was identified in the compound of FEA of curcuma and FEA of bitter melon at the dose of 20: 0,2m9g/200g BB in the rats with HFD- fructose.